To solve the equation \(-3(-4x - 3) = -27\), we can follow these steps:
-
Distribute \(-3\) on the left side: \[ -3 \cdot -4x - 3 \cdot -3 = 12x + 9 \] So, the equation becomes: \[ 12x + 9 = -27 \]
-
Next, we will subtract \(9\) from both sides: \[ 12x + 9 - 9 = -27 - 9 \] This simplifies to: \[ 12x = -36 \]
-
Now, divide both sides by \(12\): \[ x = \frac{-36}{12} \] This simplifies to: \[ x = -3 \]
Thus, the solution is \(x = -3\).
In the format you've shown, the response is: x=−3 (x equals negative 3).